Use of Doppler Ultrasound in Perinatal Care: Maternal and Neonatal Care - Karolina Zalewa; Joanna Olszak; Marta Kaus; Dominika Orłowska; Lidia Bartoszek; Mikołaj Poleszczuk; Karol Poleszczuk; Anna Czuba; Alicja Milewska; Natalia Klepacz (Journal of Education, Health and Sport)
Introduction and purpose